Pendekatan Regresi Linear Berganda untuk Estimasi Pengeluaran per Kapita di Desa dan Kota untuk Wilayah Sumatera Utara - Agnes Tri Abiya Perangin-angin; Elsa Adella Siburian; Geri Juna Putra Orando Purba; Jeffry Delay Silaban; Raisa Delvina Pakpahan; Theodora Risma Naftali; Indra M. Sarkis S. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The level of community welfare can be seen from economic factors. To find out the economic welfare of the community requires the calculation of per capita expenditure. Identifying per capita expenditure estimates can be a reference for the government and a company to find out the economic dynamics of the community. The expenditure data is per capita expenditure in villages and cities for the North Sumatra region, this data is taken from the BPS website. In estimating using the Multiple Linear Regression method and to analyze its accuracy using MAPE analysis. The results of estimation with multiple linear regression on per capita expenditure in villages and cities in North Sumatra for 2024 are 11,182, and the value obtained from the calculation with MAPE is 0.933% which means the accuracy level is 99.067%.